The Power of Debate in Conflict-Affected Communities: Fostering Civic Engagement and Active Citizenship in Libya - Huda Abdelhalim Alarousi (22590440) (2025)
This conference contribution was presented by Huda Abdelhalim Alarousi, Abdulrauf El-Geroshi. Dialogue and Debate Association, Libya (International Conference on Debate and Dialogue. An Initiative of QatarDebate 2025). This study explores the transformative role of debate in fostering civic competencies, ethical reasoning, and public engagement among youth in conflict-affected contexts, with a focus on Libya. Using a field-based methodology, data were collected from diverse participants involved in debate activities, including leaders, instructors, and debaters, across Libya’s regions. The findings reveal that debate enhances critical thinking, empathy, and democratic values, while promoting social cohesion and reducing divisive narratives. Despite its potential, challenges such as competitiveness require careful program design. The study underscores debate as a vital tool for empowering youth, and cultivating informed, active citizens in post-conflict societies. Other Information Conference information: The 2nd International Conference on Debate & Dialogue : An Initiative of QatarDebate (19 - 20 May 2025, Qatar National Conventions Center - QNCC, Doha - Qatar) License: https://creativecommons.org/licenses/by/4.0/ See the conference information on the organizer's website: https://qatardebate.org/programs/academic-programs/2nd-icdd/